Models of risk preferences : descriptive and normative challenges - Harrison, Glenn W.; Ross, Don (Emerald Publishing Limited, 2023)
Behavioural economists have developed alternatives to Expected Utility Theory as descriptive and normative models of risk preferences. One popular view is that these alternative descriptive models are generally better descriptively, but that they tend to be inferior normative models for guiding risky decisions. Models of Risk Preferences collects studies that critically review these two claims from the perspective of experimental economics. The Research in Experimental Economics series focuses on laboratory experimental economics, but includes theoretical, empirical, or field economic research to encompass the broader experimental economics community.
Includes index.
Keywords: Risk -- Psychological aspects.; Risk -- Mathematical models.; Utility theory -- Mathematical models.; Business & Economics -- Insurance / Risk Assessment & Management.; Risk assessment.; elektronické knihy; electronic books